Richer (and Holier) Than Thou? The Effect of Relative Income Improvements on Demand for Redistribution - Karadja, Mounir; Mollerstrom, Johanna; Seim, David (The Review of Economics and Statistics, 2017)
We use a tailor-made survey on a Swedish sample to investigate how individuals' relative income affects their demand for redistribution. We first document that a majority misperceive their position in the income distribution and believe that they are poorer, relative to others, than they actually are. We then inform a subsample about their true relative income and find that individuals who are richer than they initially thought demand less redistribution. This result is driven by individuals with prior right-of-center political preferences who view taxes as distortive and believe that effort, rather than luck, drives individual economic success.